The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1109/comst.2016.2633579
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Contributions of Software-Defined Networking to Traffic Engineering

Abstract: Since the appearance of OpenFlow back in 2008, Software-Defined Networking (SDN) has gained momentum. Although there are some discrepancies between the standards developing organisations working with SDN about what SDN is and how it is defined, they all outline Traffic Engineering (TE) as a key application. One of the most common objectives of TE is the congestion minimisation, where techniques such as traffic splitting among multiple paths or advanced reservation systems are used. In such a scenario, this man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 133 publications
0
68
0
8
Order By: Relevance
“…As recent surveys have indicated, there is no standard to exchange network control information between different SDN controllers [40,48], although some initiatives have tried to standardize an East/Westbound for SDN controllers, for example, ALTO [4,49].…”
Section: East/westbound Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recent surveys have indicated, there is no standard to exchange network control information between different SDN controllers [40,48], although some initiatives have tried to standardize an East/Westbound for SDN controllers, for example, ALTO [4,49].…”
Section: East/westbound Discussionmentioning
confidence: 99%
“…The evaluation metrics for the SDN protocols were highlighted by the survey of Mendiola et al [4] who indicated that the number of messages and the size of the messages were criteria for the measurement scalability of the SDN solutions. Based on this claim, the signaling overhead was measured of the proposed architecture for the size of East/Westbound messages.…”
Section: Signaling Overheadmentioning
confidence: 99%
“…This is done by applying a hash function over the set of packets' header fields. Since OpenFlow switches can use a wide range of classifiers to forward packets [11], fine-granularity of traffic splitting is expected [5]. Unequal traffic splitting ratios could be implemented with Group tables in the processing pipeline of OpenFlow switches [11].…”
Section: The Network Modelmentioning
confidence: 99%
“…However, PCE based architecture also suffers from slow path establishment issues, since it relies on distributed Resource Reservation Protocol (RSVP-TE) to set up, maintain and tear down traffic tunnels. Moreover, from the TE perspective, there is an issue with per-flow traffic splitting granularity in multipath routing, which is determined by the forwarding element capabilities and might deviate significantly from that assumed by TE solution [5]. This motivated emergence of Software Defined Networking (SDN) architecture with out-of-band programming capabilities and higher granularity of traffic control [5].…”
Section: Introduction Ith the Evolution Of Internet Of Things (Iot)mentioning
confidence: 99%
“…Due to its promising architecture, which enabled ease of management and innovation, a multitude of uses-cases have been devised for SDN including but not limited to Internet-of-Thing (IoT) [22], [104], Wide Area Network (WAN) [73], traffic engineering [72], mobile networks [47] and 5G [25], [62], [103], and network isolation and slicing [88].…”
Section: Chapter 2 Backgroundmentioning
confidence: 99%